Extremely short duration high intensity training significantly improves endurance performance and blood lactate profiles in triathletes - Jakeman, J. R.; Adamson, S.; Babraj, J. A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
It has been demonstrated that high intensity training (HIT) involving 30 second sprints is an effective approach to improving aerobic performance (Burgomaster et al., 2005). The magnitude of this effect may be due to increased glycogen turnover (Babraj et al., 2007), and therefore, the same benefits should be achieved from shorter duration sprints. We investigated whether shorter duration HIT, involving 6 second sprints, improved aerobic performance. Methods: Twelve competitive, male triathletes (35 ± 8 y, weight 82 ± 10 kg, BMI 26 ± 3 kg.m-2) participated in the study and were allocated to either a training group (n=6) performing two weeks of HIT, or a control group (n=6). The HIT intervention involved 10 x 6 sec sprints separated by 1 min rest, 3 x per week for 2 weeks (totalling 6 sessions, with a total exercise time of 6min). Before and after 2 weeks of HIT or normal activity (control), participants completed a self paced 10km time trial and a time to exhaustion (TTE) test on a cycle ergometer. Blood lactate concentration was taken throughout the TTE using finger prick blood samples. Results: Two weeks of HIT resulted in an 11% decrease in self paced 10km time trial (p= 0.004) but no change in time to exhaustion. The time taken to reach onset of blood lactate accumulation (OBLA, defined as the point where blood lactate reaches 4mmol/l) was significantly increased following 2 weeks of HIT (p = 0.004). Total work done in a 10 x 6 second training session was 50 ± 9 kJ, in comparison with 64 ± 13 kJ for a 4 x 30 second training session (p = 0.05) Discussion: In the present study we demonstrate for the first time that only 3 minutes of high intensity exercise per week over two weeks significantly improves aerobic performance with an attenuation of blood lactate accumulation normally seen following longer duration of sprints (Burgomaster et al., 2005). Though not quantified, all participants reported lower perceptions of exertion following sprints of 6 second than typically observed in our laboratory during 30 second sprints. The similarity of response between the 6 and 30 second sprint training regimens suggests that the performance adaptation to HIT is likely to be driven by glycogen depletion. In conclusion, lower duration sprints are a viable alternative to 30 second sprints for promoting improved aerobic performance in triathletes.